Penurunan Kerusakan Jaringan Paru Terinfeksi Tuberkulosis oleh Ekstrak Pegagan Melalui Peningkatan Ekspresi Tissue Inhibitor of Matrix Metalloproteinase-1 (SUPLEMENTATION OF EFFECT ANILYSIS OF CENTELLA ASIATICA EXTRACT IN REDUCE LUNG TUBERCULOSIS TISSUE D - Mustika, Arifa; Rahaju, Anny Setijo; Indrawati, Roostantia (Jurnal Veteriner, 2015)
Centella asiatica is a medicinal plant used for wound healing through increasing of collagen synthesis.This evidence generates a new expectation that it could be used for therapy of tuberculosis infection,especially for healing lung tissue damage. Until now, the effects and mechanisms onC. asiatica to cure thelung tissue damage due to M. tuberculosis infection remains unclear. The aim of this study was to prove theeffect and mechanism of ethanol extract of C. asiatica to repair the rats lung tissue damaged throughexpression of the enzimmatrix metalloproteinase-1(MMP-1)danenzimtissue inhibitor of matrixmetalloproteinase-1 (TIMP-1). The study was conducted in male rats. Twenty four rats were infected withM. tuberculosis through intratrachea and randomly divided into four groups. Group 1, 2 and 3 were thetreatment groups that they were given the ethanol extract of C. asiatica at dose 375mg/kgbw, 750 mg /kgbw, and 1500 mg / kgbw, orally and once a day for fourteen days. The fourth group was a control groupthat given distilled water. On day 15 rats were euthanized and lungs tissue have been taken. Evaluationof lungs tissue damage were assessed by the Dorman’s score in Hematoxylin Eosin and evaluation of the expression of MMP - 1 and TIMP 1 were performed by immunohistochemistry. Data of TIMP-1 wereanalyzed with ANOVA and data of lung tissue damage and MMP–1 were analyzed with Mann WhitneyU (á = 0.05). The results showed that there was a significant differences in the lungs tissue damagebetween the dose groups of 375 mg / kgbw and controls (p = 0.006), the dose groups at dose 750 mg / kgbwand controls (p = 0.004 ), the dose groups of 1500 mg / kgbw and controls (p = 0.043). There wasn’t asignificant difference between the treatment groups and control in the expression of MMP-1. In the expressionof TIMP – 1, there was a significant difference between the treatment group at dose of 750 mg / kg andcontrol. The conclusion of the study is the ethanol extract of C. asiatica has the ability to reduce lung tissuedamage of rats infected with M. tuberculosis, through increasesthe expression of TIMP-1
Keywords: C. asiatica, M. tuberculosis, lung, MMP-1, TIMP-1